Kossmaticeratidae (Ammonitina) y nomenclatura estratigráfica del Cretácico tardío en Lago Argentino, Santa Cruz, Argentina - Riccardi, Alberto Carlos (1983)
Outcrops located on the banks of the Calafate creek, southern margin of Argentine) lake have yielded: Kossmaticeras (Karapadites) centinelaense Blasco et al., K. (Natalites) cf. hauthali (Paulcke), Neograluimites morenoi sp. nov. These fossils indicate an early (middle) Campanian age for the upper part of the pelitic sequence, i.e. Cerro Toro Formation, immediately below the Maastrichtian (?) Anita Formation. In relation to the already known ammonite faunas from Patagonia, this one is older that those containing Maorites Marshall and Hoplitoplacenticeras Paulcke, and younger than that bearing Anapachycliscus Yabe and Shimizu.